Greening Semiotizations: The Ecocritical-Biosemiotic Literacies of Selected Ecopoems from Sustaining the Archipelago: Philippine Ecopoetry Anthology - Jan Raen Carlo Mijaro Ledesma (Journal of Language and Literature, 2024)
This paper is an attempt to flesh out the biosemiotic and ecological literacies of selected ecopoems from the collection Sustaining the Archipelago: An Anthology of Philippine Ecopoetry (2017). I recognize the biosemiotic fact that every living organism of nature possesses the ability to inventively pursue their environments made possible through an active engagement of signs in the environment. Grounded on the ecocritical theories of Hubert Zapf, David Orr and Jacob von Uexkull and the descriptive-analytical research design, I analyze Philippine ecopoetry and how it can substantially bring readers within the environment itself and experience its attendant forces shaping it on both micro and macro heights. Ecopoetry allows us to better comprehend the particularities and complexities of the environment and the workings of our biologies. It positions its readers within the intricate spheres of the environment. Echoing the concept of ecological literacy, the reader becomes more knowledgeable and intimate with the environmental space recreated through the words of the poet. In the analysis, I recognize the ecoliterate affinities of the poets and their works highlighting ecocritical discourses on biophilia, topophilia, topophobia, anthropocentric activities, holism and systems thinking. These affinities are further dissected with the aid of biosemiotics. Biosemiotics looks into the complexities of the environment emphasizing various significant organisms and occurrences that shape environmental connections and disconnections. In the ecopoems, there are signs and occurrences that can be specifically interpreted shaping environmental connections. These are essential in understanding the processes that make nature and culture experience connections and disconnnections.